2002
DOI: 10.1002/chem.200390018
|View full text |Cite
|
Sign up to set email alerts
|

Amination of Benzylic CH Bonds by Arylazides Catalyzed by CoII–Porphyrin Complexes: A Synthetic and Mechanistic Study

Abstract: Co(II)-porphyrin complexes catalyze the reaction of aromatic azides (ArN(3)) with hydrocarbons that contain a benzylic group (ArR(1)R(2)CH) to give the corresponding amines (ArR(1)R(2)C-NHAr). When at least one of the R substituents is hydrogen, the catalytic reaction proceeds further to give the imine ArRC=NAr in good yields. The reaction mechanism has been investigated. The reaction proceeds through a reversible coordination of the arylazide to the Co(II)-porphyrin complex. This unstable adduct can either re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
138
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 207 publications
(147 citation statements)
references
References 101 publications
7
138
0
2
Order By: Relevance
“…Any attempt to spectroscopically observe the species [(ArN 3 )Ru(TPP)(CO)] failed. Evidence that an imidometal complex is not always the group transfer reagent has already been provided by the amination of benzylic groups and by the aziridination of styrenes cata-lyzed by [Co II (porphyrin)] [55,56] and [Mn III (corrole)] [64] complexes, respectively.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Any attempt to spectroscopically observe the species [(ArN 3 )Ru(TPP)(CO)] failed. Evidence that an imidometal complex is not always the group transfer reagent has already been provided by the amination of benzylic groups and by the aziridination of styrenes cata-lyzed by [Co II (porphyrin)] [55,56] and [Mn III (corrole)] [64] complexes, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…Moreover, it is important to point out that the aryl group on the aziridine nitrogen atom should be considered as part of the molecule that can play an important role in further aziridine rearrangements. [53,54] Aryl azides react with benzylic C-H bonds to form amines and imines, [55,56] with conjugated dienes to give Naryl-2-vinylaziridines [54] and with styrenes to form N-arylaziridines. [57] The amination reactions of benzylic com-pounds are catalyzed by [Co(porphyrin)] complexes and the aziridination reactions are efficiently catalyzed by [Ru(porphyrin)CO] complexes.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Only very electrophilic nitrenes yield the C À H insertion product with hydrocarbon solvents in appreciable amounts. [11][12][13][14] The current state of the art [15] in the amidation of C À H bonds thus relies on nitrene surrogates, for example iminoiodanes PhI=NR [16] and aryl azides, [17] in transition-metalmediated reactions, although metal-free conversions are also known. [18] The groundbreaking work goes back to Breslow and co-workers, [19] who demonstrated in 1982 that cyclohexane can be amidated in 3-6 % yield based on the iminoiodane in the presence of metal porphyrins.…”
mentioning
confidence: 99%
“…[21,22] In fact, we have reported that cobalt supported on carbon was a highly active and selective catalyst in the catalytic oxidation of o-cresol with molecular oxygen to form salicylaldehyde. [23] However, when the cobalt catalyst was adopted in the oxidation of p-cresol, the selectivity for p-hydroxybenzaldehyde was relatively low.…”
Section: Introductionmentioning
confidence: 99%